Faktor Resiko Kejadian Kejang Demam pada Balita di Wilayah Kerja Puskesmas Wali Kecamatan Binongko Kabupaten Wakatobi - Masriwati, Sitti; Jefri, La Ode (Jurnal Gizi Ilmiah, 2016)
Data from the Wali Health Center showed that in 2014 from 230 toddlers, 21 children under five suffered from febrile seizures. In 2015 from 225 children under five, the number of patients with febrile seizures was 38 children under five. Based on the results of interviews conducted by researchers from 10 mothers who have toddlers with a history of febrile seizures, there are 4 mothers who say their children often have febrile seizures which always begin with a fever with a temperature above 380 C and 4 mothers say that there are other family members who often experience fever. febrile seizures and 2 people said they had febrile seizures because their nutritional status was not good. This study aims to determine the risk factors for the occurrence of febrile seizures in toddlers in the work area of ​​the Wali Health Center, Binongko District, Wakatobi Regency. This type of research is observational analytic research, with the research design used is a case control study. The population is all toddlers who have a history of fever, namely 38 toddlers in the work area of ​​the Wali Health Center, Binongko District, with a total sample of 35 cases and 35 controls so that the total is 70 toddlers. The method of analysis using the Odds Ratio Test. The results showed that body temperature was a risk factor for the occurrence of febrile seizures in toddlers in the work area of ​​the Wali Health Center, Binongko District, Wakatobi Regency (OR = 22,389; CI = 95%), heredity was a risk factor for the occurrence of febrile seizures in toddlers in the work area of ​​the Wali Subdistrict Health Center. Binongko, Wakatobi Regency (OR= 4,500; CI= 95%), the history of neonates is a risk factor for the incidence of febrile seizures in children under five in the working area of ​​the Wali Health Center, Binongko District, Wakatobi Regency (OR= 1,938; CI= 95%), and nutritional status is a risk factor. The incidence of febrile seizures in toddlers in the work area of ​​the Wali Health Center, Binongko District, Wakatobi Regency (OR = 5,712; CI = 95%) It is hoped that the Wali Health Center will provide health information about febrile seizures in toddlers, put up posters at the Puskesmas and provide counseling in the community about the importance of preventing cases of febrile seizures in toddlers, especially with regard to body temperature, hereditary history , neonatal history, and nutritional status